2022
DOI: 10.3390/nano12101654
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemistry Study on the Structures and Electronic Properties of Bimetallic Ca2-Doped Magnesium Ca2Mgn (n = 1–15) Clusters

Abstract: Here, by utilizing crystal structure analysis through the particle swarm optimization (CALYPSO) structural searching method with density functional theory (DFT), we investigate the systemic structures and electronic properties of Ca2Mgn (n = 1–15) clusters. Structural searches found that two Ca atoms prefer to occupy the external position of magnesium-doped systems at n = 2–14. Afterward, one Ca atom begins to move from the surface into the internal of the caged skeleton at n = 15. Calculations of the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In cluster structure prediction, many studies have successfully revealed its validity. [42][43][44][45][46][47][48][49][50] For each cluster size, there are more than 800 structurally different isomers located at 20 generations. It provides 50 structures in each generation, 70% of which are generated by PSO and the rest are newly produced.…”
Section: Methodsmentioning
confidence: 99%
“…In cluster structure prediction, many studies have successfully revealed its validity. [42][43][44][45][46][47][48][49][50] For each cluster size, there are more than 800 structurally different isomers located at 20 generations. It provides 50 structures in each generation, 70% of which are generated by PSO and the rest are newly produced.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, numerous structures based on the CALYPSO searching method have been executed successfully for clusters, two-dimensional materials, functional materials and crystals. 39–51 The detailed searching process could be summarized as follows: first, the PBE/3-21G level was used for the preliminary structures. Second, according to the parameters of generation (50) and maxstep (20), about 1000 initial structures can be obtained.…”
Section: Methodsmentioning
confidence: 99%